Growth analysis, mortality and exploitation level of Mud Crab Scylla serrata, Forskål 1775, (Malacostraca : Portunidae) in Mangkang Wetan waters, Semarang, Central Java, Indonesia - Ervia Yudiati; Arumning Tias Fauziah; Irwani Irwani; Agus Setyawan; Insafitri Insafitri (Jurnal Kelautan Tropis, 2020)
Awareness of Mud Crab over exploitation in Mangkang Wetan Waters has been noticed. One of the reference information is the growth study to determine the condition of the mud crab population. High demand encourages the fisherman to catch more, which leads to overexploitation in nature. The study aimed to estimate the growth, mortality, and exploitation rate of mud crabs. The 921 mud crabs samples were collected from Mangkang Wetan Waters from October 2018 to January 2019. The method used was the survey method. The crabs were taken once a week for 4 months. The width and weight of crab carapace were measured. The growth rate of S. serrata was 0.93/year (male) and 0.69/year (female). The natural mortality rate of S. serrata was 1.08/year (male) and 0.89/year (female), the mortality of catch (F) was 0.55/year (male) and 1.09/year (female). The rate of exploitation of male S. serrata reached 34%, and the rate of exploitation of female S. serrata was 55%. The exploitation of female S. serrata shows that overexploitation has occurred because the optimum value of exploitation (E-OPTIMUM) is equivalent to E=50%.